A Phase II prospective nonrandomized trial of magnetic resonance imaging-guided hematopoietic bone marrow-sparing radiotherapy for gastric cancer patients with concurrent chemotherapy - Wang, Jianyang (Onco Targets Ther, 2016)
PURPOSE: This study aimed to spare hematopoietical bone marrow (BM) identified by magnetic resonance (MR) radiation in order to alleviate acute hematologic toxicity (HT) for gastric cancer patients treated with postoperative chemoradiotherapy (CRT). METHODS: A prospective, open-label, single-arm Phase II study (Clinicaltrials.gov; NCT 01863420) was conducted in 25 patients with gastric cancer who were eligible for postoperative concurrent CRT. The MR images of vertebral body T8-L4 were fused with images of simulating computed tomography. Hematopoietical BM was contoured according to the MR and spared in radiotherapy plan. The CRT regimen consisted of daily capecitabine (1600 mg/m(2)/d) and 45 Gy of radiation at 1.8 Gy per day. Primary endpoints were grade ≥3 HT that occurred within 2 months of initiation of CRT. The relationship between HT and dose–volume of BM was estimated by multivariable linear regression model. RESULTS: Twenty four patients (96%) had T3–4 disease and 22 (88%) had disease with node positive. The median age was 53 years (range, 28–73 years). Before concurrent CRT, adjuvant chemotherapy was administered with a mean cycle of 4.3±0.5. Only five patients (20%) developed grade 3–4 HT during treatment, among whom two (8.0%) patients experienced grade 3–4 leucopenia, two (8.0%) experienced neutropenia, and two (8.0%) experienced thrombocytopenia, respectively. None of the patients showed grade 3–4 anemia. Multivariable linear regression revealed increased BM-V5 (P=0.03) and BM-V20 (P=0.002) were found to be significantly associated with decreased white blood cells nadirs in multivariable regression; increased BM-V20 (P<0.001) with decreased absolute neutrophil count nadirs, increased BM-V30 (P=0.002) and volume of BM (P=0.001) with decreased platelet count nadirs. CONCLUSION: Irradiation of active BM identified by MR is associated with HTs. Techniques to limit low-dose radiation, especially V20, to BM could reduce HT in gastric cancer patients.